A midsummer night's dream - Shakespeare, William, 1564-1616.; Buckle, Linda (Cambridge ; New York : Cambridge University Press, 2005)
An edition of Shakespeare's comedy, including discussion of its production, themes, patterns, language, and author.
Keywords: Children's plays, English; Fairy plays; Courtship -- Juvenile drama; Fairies -- Drama; Plays; Athens (Greece) -- Juvenile drama